2010
DOI: 10.1097/won.0b013e3181e45774
|View full text |Cite
|
Sign up to set email alerts
|

The Association of BMI and Braden Total Score on the Occurrence of Pressure Ulcers

Abstract: A BMI of more than 40 and Braden Scale score of 16 or less were found to have an independent and statistically significant association with PU occurrence. Future studies should investigate the predictive validity of BMI along with individual Braden subscales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 17 publications
0
42
0
Order By: Relevance
“…This finding is consistent with the US data from an international pressure ulcer prevalence survey in which the prevalence of pressure ulcers was higher in underweight and extremely obese patients. 6,32 The underweight and extremely obese groups did not differ in race/ethnicity, total scores on the Braden scale, incidence of pressure ulcers, length of ICU stay, or discharge disposition; however, differences in sex and mean age were significant. Compared with patients in the other groups, extremely obese patients were 4 to 5 years younger and more likely to be women.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…This finding is consistent with the US data from an international pressure ulcer prevalence survey in which the prevalence of pressure ulcers was higher in underweight and extremely obese patients. 6,32 The underweight and extremely obese groups did not differ in race/ethnicity, total scores on the Braden scale, incidence of pressure ulcers, length of ICU stay, or discharge disposition; however, differences in sex and mean age were significant. Compared with patients in the other groups, extremely obese patients were 4 to 5 years younger and more likely to be women.…”
Section: Discussionmentioning
confidence: 77%
“…23 In addition, obesity among patients is a main reason for injuries among care providers. 19 Extreme obesity has been associated with an increased prevalence of pressure ulcers in patients in a tertiary medical center, 6 and among elderly patients, pressure ulcers are less likely to develop in nonobese patients 24,25 and in general surgery patients. 23 In critical care, BMI has been associated with the development of pressure ulcers in patients treated with mechanical ventilation who had acute lung injury.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Kottner et al indicated that the etiology and pathogenic mechanisms of the development of pressure ulcers on the trunk and heel may be different. Furthermore, in a comparison of the prevalence of pressure ulcers in patients with a BMI of 40 or more and Braden Scale scores of 16 or more with the prevalence in patients with lower BMI, Drake et al 25 found that the prevalence among patients with a BMI less than 40 was 12.5% compared to a prevalence of 26% in patients with a BMI greater than 40 ( P = .01). Patients with BMIs greater than 40 were almost 3 times more likely to have a pressure ulcer than were patients with BMIs of 40 or less, after controlling for scores on Braden Scale indicative of risk ( P = .01).…”
Section: Discussionmentioning
confidence: 99%
“…Morbid obesity has been associated with longer ICU length of stay and prolonged mechanical ventilation, with increased overall mortality and ICU mortality currently under debate [7], [8]. Factors contributing to ICU mortality in extreme-obesity include increased catheter and blood stream infections [9], limited imaging modalities, increased skin breakdown [10], and diagnostic errors. Additionally, a condition called MOHS was recently described [11].…”
Section: Introductionmentioning
confidence: 99%